Incidence and risk factors of post-tonsillectomy haemorrhage in patients operated during the 2012-2016 period at ENT Department Hospital Serdang, Malaysia - Sethu T. Subha,; Atiqah Farah Z.,; Chong, K.M.; Nor Ashikin A.H.,; Muhammad Fikri S., (Penerbit Universiti Kebangsaan Malaysia, 2019)
Tonsillectomy is the most common operation performed in the field of Ear, Nose and Throat (ENT) Surgical speciality. Post-tonsillectomy haemorrhage remains a significant complication leading to morbidity and occasional mortality. The main objective of this study was to evaluate the incidence and risk factors of post-tonsillectomy haemorrhage in a cohort of patients who had been operated at our institution. This retrospective cohort study reviewed the medical records of all patients who underwent tonsillectomy from 1st January 2012 to 31st December 2016. Data on patient’s age, gender, race, smoking habit, indication for tonsillectomy, duration and technique of surgery, usage of post-operative drugs and management were recorded. Out of 315 patients included this study, 54.9% were adults (12 years and above) and majority (86.3%) of them were of Malay descent. The common indication for tonsillectomy was recurrent tonsillitis (84.4%). This study showed significant associations (p<0.05) between age, smoking and the use of steroids with post-tonsillectomy haemorrhage. However, there was no significant association between gender, race, use of post-operative drugs (non-steroidal anti-inflammatory drugs, antibiotics), duration of surgery, the technique of surgery and post-tonsillectomy haemorrhage. The incidence of post-tonsillectomy haemorrhage in our population was 10.5% (n=33) and among them, 54.5% (n=18) required surgical intervention. Our study demonstrated that older patients (12 years and above), smokers and the use of steroids during the post-operative period have increased the risk of post-tonsillectomy haemorrhage. An awareness of these risk factors should help to minimize the post-tonsillectomy haemorrhage and improve the patient outcomes.